Judicialização da política e ativismo judicial: uma violação ao princípio da separação dos poderes ou uma necessidade para a efetivação plena dos direitos fundamentais na sociedade brasileira contemporânea? - Neves, George Hilton Lemos (2021)
The present work deals with the institutional rise of the Judiciary in the contemporary Brazilian scenario, especially with regard to the judicialization of politics and judicial activism, highlighting the preponderance that this constitutionally established institution has acquired over the years, assuming extreme importance within of society, playing an active role in the implementation of Fundamental Rights, whether by suppressing omissions or correcting distortions resulting from the performance of the Legislative Power with regard to the elaboration of norms, or of the Executive Power with regard to the execution of public policies. In this context, the principles of the Supremacy of the Constitution and the Separation of Powers will be addressed, as well as the historical evolution of State models to the present day, relating these aspects to the issue of the realization of Fundamental Rights. The research took as its starting point the question regarding the following problem: the judicialization of politics and judicial activism in the Brazilian Democratic State of Law are appropriate phenomena to achieve the full realization of Fundamental Rights or would they be violating the principle of Separation of Powers? The study of the selected theme is important because this preponderance of the Judiciary is causing relevant tension between the State Powers, bringing up the discussion about the harmony of Powers and the survival of democratic principles, giving rise to a complex debate about this more active action. of the Judiciary, which brings relevant political, economic and social impacts to the population and which are directly related to the realization of the Fundamental Rights constitutionally foreseen, essential to provide a dignified life to all citizens. Faced with the presented problem, the main objective of the work is to analyze the phenomena of the judicialization of politics and judicial activism in contemporary Brazil, based on the principle of the Separation of Powers, confronting it with the need for the full realization of Fundamental Rights, the in order to establish what should prevail in cases in which they appear to be conflicting. The methodology used to carry out the research consists of an applied research, with a hypothetical-deductive and qualitative approach, with a descriptive objective. Also using the dialectical and historical method. At the end of the research, after carrying out the considerations for and against the institutional rise of the Judiciary, it was concluded that, despite the apparent instability that the judicialization of politics and, mainly, judicial activism, in the usual conception of the term, can bring to the spheres of power, the performance of the judiciary is extremely relevant in the search for the effective protection of Fundamental Rights and the Democratic State of Law, since when the guarantee of Fundamental Rights is pursued, embodied in the text of the Federal Constitution 1988, the Judiciary can and, not infrequently, has the obligation to participate in the typical decisions of other branches of the State without this implying in an affront to the principle of Separation of Powers, since the most active posture of the judiciary has its legitimacy based, formally, in the Constitution itself and, materially, in the need to protect the Democratic State Law and the Fundamental Rights.